The Effect of Platelet Aditive Solution In Maintaining the Quality and Function of Concentrated Platelets In The Pooling Method of Buffy Coat Leukofiltered - Wido Sari Nawangsih, Idah; Widia A. Jusman, Sri; Chunaeni, Saptuti (Jurnal Health Sains, 2025)
The availability of platelets in the Indonesian Red Cross (PMI) Blood Transfusion Unit (UDD) has been significantly high, with 767,680 bags collected in 2019, increasing to 957,397 bags in 2021. The dengue fever outbreak alongside the COVID-19 pandemic led to a nearly twofold increase in the demand for concentrated platelets (TP) in hospitals from 2021. However, platelet additive solution (PAS), which can extend platelet shelf life, is not yet utilized in Indonesia. This study aims to investigate whether TP obtained using the buffy coat leukofiltered pooling method and stored with PAS can improve platelet quality during storage. A series of laboratory tests were conducted to evaluate platelet count, pH levels, and aggregation function using ADP inspection, monitored over a storage period from day zero to day seven. The results indicate that the addition of PAS effectively maintains platelet quality, pH stability, and platelet function throughout the storage duration. This is attributed to the nutrient-rich composition of PAS, which contains glucose, sodium acetate, sodium chloride, phosphate, magnesium, and potassium, ensuring the preservation of platelet integrity. The findings highlight the potential benefits of PAS implementation in Indonesia to enhance platelet storage efficiency and availability, particularly during periods of high demand. Future research should explore the optimal PAS formulation for different storage conditions, cost-effectiveness, and clinical efficacy in transfusion settings to support broader adoption of this technology in blood banking.